Manganese oxide heterojunction / expanded graphite composite material and preparation method thereof, negative electrode for lithium ion battery, and lithium ion battery
Patent Information
- Application Number
- CN202611115543.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-16
AI Technical Summary
以解决传统制备工艺繁杂、制备条件比较苛刻且异质结构筑困难的技术问题
[0025]1.工艺极其简单,成本低廉,易于宏量制备。本申请采用一步球磨法,原料为商业化产品,无需复杂的预处理、后处理(如高温退火),流程短,设备要求低,能耗少,非常适合于大规模生产。
Smart Images

Figure CN122930870A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of energy storage materials technology, and in particular to a manganese oxide heterojunction / expanded graphite composite material and its preparation method, a negative electrode for lithium-ion batteries, and lithium-ion batteries. Background Technology
[0002] Lithium-ion batteries, due to their high energy density and long cycle life, have become core energy storage devices in portable electronic devices, electric vehicles, and large-scale energy storage. As a key component of lithium-ion batteries, the performance of the anode material directly determines the battery's energy density, power density, and cycle stability. Currently, commercially available graphite anode materials have a relatively low theoretical specific capacity (approximately 372 mAh g⁻¹). -1 This technology is no longer sufficient to meet the needs of the next generation of high-energy-density batteries.
[0003] Transition metal oxides, especially manganese oxides (including MnO, Mn3O4, Mn2O3, MnO2 and their mixtures), have high theoretical specific capacities (700~1200 mAh g⁻¹). -1 With its advantages of abundant resources and environmental friendliness, it is considered a highly promising next-generation anode material. However, it suffers from severe volume expansion during charge and discharge, leading to the pulverization and detachment of the active material and loss of electrical contact with the current collector; simultaneously, its low intrinsic electronic conductivity results in poor rate performance. These problems severely restrict its practical application.
[0004] To overcome the above defects, a common strategy is to combine it with carbon materials (such as graphene, carbon nanotubes, porous carbon, etc.). The carbon material matrix can effectively buffer volume changes, inhibit particle agglomeration, and provide an efficient electronic conductivity network. At present, the preparation methods of manganese oxide / carbon composite materials mainly include hydrothermal / solvothermal methods, coprecipitation methods, high-temperature solid-state methods, etc. However, these methods usually have some inherent limitations: (1) Complex process: often requires multiple steps of reaction (such as precursor preparation, carbon coating, etc.), involving high-temperature annealing or harsh reaction conditions, high energy consumption and long cycle; (2) Difficult to control structure, it is difficult to achieve uniform and compact composite of manganese oxide and carbon matrix at the nanoscale, and it is difficult to construct heterogeneous structures.
[0005] Therefore, developing a simple, mild method for preparing manganese oxide / carbon composite materials that can precisely construct strongly coupled heterogeneous interfaces at the atomic / nanoscale is of great significance for promoting the practical application of high-performance transition metal oxide anode materials. Summary of the Invention
[0006] Therefore, the purpose of this application is to overcome the shortcomings of the prior art and provide a manganese oxide heterojunction / expanded graphite composite material, its preparation method, a negative electrode for lithium-ion batteries, and a lithium-ion battery. This addresses the technical problems of complex traditional preparation processes, demanding preparation conditions, and difficulties in constructing heterostructures.
[0007] To achieve the above objectives, this application adopts the following technical solution:
[0008] First, this application provides a method for preparing a manganese oxide heterojunction / expanded graphite composite material, comprising the following steps:
[0009] Expanded graphite, manganese monoxide, and a liquid medium are mixed and then subjected to mechanochemical ball milling to obtain a manganese oxide heterojunction / expanded graphite composite material. The mechanochemical ball milling is carried out in a planetary ball mill at a speed of 200-800 rpm for 2-48 hours.
[0010] As an example, the rotational speed of the ball mill can be 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, or 800 rpm; or it can be a range of values formed by any two of the above values as endpoints.
[0011] As an example, the ball milling time can be 2h, 4h, 5h, 8h, 10h, 15h, 20h, 25h, 30h, 32h, 35h, 38h, 40h, 45h, or 48h; or it can be a range of values formed by any two of the above values as endpoints.
[0012] Preferably, the mass ratio of expanded graphite to manganese monoxide is 1.5~4:6~8.5. By adjusting this ratio, the carbon content in the final composite material can be precisely controlled, thereby optimizing its electrochemical performance.
[0013] Preferably, the liquid medium is selected from at least one of water, ethanol, and acetone; the ratio of the total mass of the expanded graphite and the manganese monoxide to the added mass of the liquid medium is 1:0.1 to 1. The main function of the liquid medium is to regulate the rheological state of the ball milling system, promote component dispersion, and facilitate mechanical energy transfer. As an example, the ratio of the total mass of the expanded graphite and manganese monoxide to the added mass of the liquid medium can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1. It can also be any ratio within the above range.
[0014] Preferably, the mechanochemical ball milling treatment is carried out at room temperature. Room temperature in this application refers to 20-30°C.
[0015] Preferably, the mechanochemical ball milling process is carried out under air conditions.
[0016] Preferably, in the mechanochemical ball milling process, the grinding balls are made of agate; the ratio of the total mass of expanded graphite, manganese monoxide, and liquid medium to the amount of grinding balls added is 1:5 to 50. As an example, the ratio of the total mass of expanded graphite, manganese monoxide, and liquid medium to the amount of grinding balls added can be 1:5, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, or 1:50; or any ratio within the above range.
[0017] Preferably, in the mechanochemical ball milling process, the grinding jar is made of agate.
[0018] Based on a general inventive concept, this application provides a manganese oxide heterojunction / expanded graphite composite material prepared according to the above-described preparation method.
[0019] Preferably, the manganese oxide heterojunction is embedded or attached to the sheet structure of expanded graphite and to the surface of expanded graphite.
[0020] Preferably, in the manganese oxide heterojunction / expanded graphite composite material, the relative contents of the two components, expanded graphite and manganese oxide heterojunction, exhibit a continuous and gradual distribution characteristic in the direction from the inside of the expanded graphite sheet to the outside of the sheet (i.e., the sheet surface and interlayer gap). Specifically, in the direction from the inside of the expanded graphite sheet to the outside of the sheet, the carbon content of the expanded graphite decreases from high to low, while the content of the manganese oxide heterojunction increases from low to high.
[0021] Preferably, the manganese oxide heterojunction includes at least two crystalline phases selected from MnO, Mn3O4, Mn2O3, and MnO2.
[0022] Based on a general inventive concept, this application also provides a negative electrode for a lithium-ion battery, the negative electrode comprising a negative electrode active material, the negative electrode active material comprising the above-mentioned manganese oxide heterojunction / expanded graphite composite material or comprising a manganese oxide heterojunction / expanded graphite composite material prepared according to the above preparation method.
[0023] Based on a general inventive concept, this application also provides a lithium-ion battery, which includes a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is used as the negative electrode of the lithium-ion battery.
[0024] Compared with the prior art, this application has the following significant advantages and beneficial effects:
[0025] 1. The process is extremely simple, low-cost, and easy to mass-produce. This application adopts a one-step ball milling method, uses commercially available raw materials, requires no complex pretreatment or post-treatment (such as high-temperature annealing), has a short process, low equipment requirements, and low energy consumption, making it very suitable for large-scale production.
[0026] 2. Innovatively Utilizing Mechanochemical Methods to Construct Heterojunctions and Gradient Structures in Situ. This application innovatively utilizes mechanochemical methods to induce solid-phase chemical reactions in a planetary ball mill by precisely controlling the milling energy. This causes partial oxidation or phase transformation of manganese monoxide under mechanical force and local thermal effects, generating manganese oxide heterojunctions in situ containing polycrystalline phases such as MnO, Mn3O4, Mn2O3, or MnO2. Unlike traditional ball milling processes that only achieve physical mixing, this mechanochemical action not only promotes the in-situ formation of heterojunctions of manganese oxide and their uniform embedding into the interlayers of expanded graphite, adhering to its sheet surfaces and edges, but also causes the composition ratio and structure of carbon and manganese oxide to exhibit a gradient distribution along the graphite sheets outwards. This forms a tight interfacial bond and a built-in electric field between the heterojunctions, effectively promoting charge transport and constituting a composition-structure gradient composite that is difficult to achieve using traditional mixing methods. The structural gradient distribution refers to the continuous change in spatial morphology from a dense, layered, and intact structure inside the expanded graphite sheets to a loose, porous structure with a large number of particles on the outside. The compositional gradient distribution refers to the continuous change in chemical composition along the same direction, where the carbon content decreases from high to low, while the manganese oxide heterojunction content increases from low to high. In other words, from the inside out, the structure changes from dense to loose, and the particle load increases; the composition changes from carbon-rich to manganese oxide-rich.
[0027] 3. The material structure has significant advantages and a prominent synergistic effect. (1) Expanded graphite as an ideal matrix: It has good conductivity and flexibility. Its unique worm-like porous structure can provide manganese oxide with abundant loading space and elastic space to buffer volume changes. (2) Strong interfacial bonding: The interfacial bonding strength formed by mechanochemical action is much higher than that of physical adsorption, which can effectively prevent the shedding of active materials during charging and discharging. (3) Synergy between gradient composite and heterojunction: The gradient structure is conducive to the smooth transition of stress distribution, while the heterojunction can improve intrinsic conductivity and ion diffusion rate. The two work together to optimize the mechanical stability and electrochemical kinetics of the material.
[0028] 4. Excellent electrochemical performance: When the composite material of this application is used as the negative electrode of lithium-ion battery, it exhibits electrochemical performance far superior to that of untreated commercial manganese monoxide and simply ball-milled manganese monoxide. Specifically, it is reflected in: (1) high reversible specific capacity; (2) excellent cycle stability, which is due to the effective buffering of expanded graphite and strong interfacial bonding that inhibits pulverization; (3) excellent rate performance, which is attributed to the good conductive network and the fast charge transfer promoted by the heterojunction.
[0029] 5. Environmentally friendly and widely applicable: The entire process can be carried out at room temperature, without the need for highly corrosive chemicals or energy-intensive equipment, making it green and environmentally friendly. This method also provides a new approach for the preparation of other transition metal oxide / carbon composite anode materials. Attached Figure Description
[0030] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0031] Figure 1 XRD patterns of MnxOy@EG-2 composite material, standard manganese tetroxide, and standard manganese monoxide.
[0032] Figure 2 SEM image of MnxOy@EG-2 composite material.
[0033] Figure 3 This is a TEM image of the MnxOy@EG-2 composite material.
[0034] Figure 4 The image shows the HRTEM image of the MnxOy@EG-2 composite material.
[0035] Figure 5 Electrochemical performance test results of lithium-ion batteries prepared from MnxOy@EG-2 composite material; among which, Figure 5 a represents the composite material used as the negative electrode in a lithium-ion battery at a current density of 0.3 A g. -1 Charge-discharge curves for different number of cycles; Figure 5 b shows the rate performance of the composite material as a negative electrode in a lithium-ion battery at different current densities. Figure 5 c represents the composite material used as a negative electrode in a lithium-ion battery at 0.3 A g. -1 Cyclic performance at current density; Figure 5 d represents the composite material used as a negative electrode in a lithium-ion battery at 1.0 A g. -1 Cyclic performance at current density. Detailed Implementation
[0036] The embodiments described in this specification are merely for explaining this application and are not intended to limit this application.
[0037] For simplicity, this specification only explicitly discloses certain numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, every point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value, or with other lower or upper limits, to form a range not explicitly stated.
[0038] Those skilled in the art will understand that the order in which the steps are written in the various embodiments or examples does not imply a strict execution order and does not limit the implementation process in any way. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, but sequentially is preferred.
[0039] The present application is further illustrated below with reference to embodiments. It should be understood that these embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0040] Example 1
[0041] S1. Accurately weigh 16 grams of expanded graphite (EG) and 24 grams of manganese monoxide (MnO) to achieve a mass ratio of 4:6. Estimate the carbon content in the manganese oxide and carbon composite material at this ratio to be approximately 40%.
[0042] S2. Place the weighed EG and MnO powders together into a 500mL agate ball milling jar containing 400g agate grinding balls, and then add 10mL of deionized water as the liquid medium.
[0043] S3. Seal and fix the grinding jar on the planetary ball mill, set the speed to 600 rpm, and continuously ball mill for 32 hours in an air atmosphere.
[0044] S4. After ball milling, open the ball mill jar and transfer the resulting slurry directly to a petri dish. Place it in an 80℃ vacuum drying oven for 12 hours to remove moisture, and finally obtain a black manganese oxide heterojunction / expanded graphite gradient composite powder, labeled as MnxOy@EG-1.
[0045] The MnxOy@EG-1 composite material was used to prepare a composite electrode: the prepared composite material, acetylene black, and polyvinylidene fluoride were uniformly mixed at a mass ratio of 80:10:10, and then N-methylpyrrolidone solution was added and a uniform slurry was formed under magnetic stirring. The slurry was coated onto copper foil and finally dried in a vacuum oven at 100°C for 12 hours to obtain the composite electrode.
[0046] Example 2
[0047] The preparation method in this embodiment is basically the same as that in Example 1, except that the added masses of expanded graphite and manganese monoxide are 12 grams and 28 grams, respectively, making their mass ratio 3:7. The carbon content of the product at this ratio is estimated to be approximately 30%. The prepared composite material is labeled MnxOy@EG-2.
[0048] Example 3
[0049] The preparation method in this embodiment is basically the same as in Example 1, except that the added masses of expanded graphite and manganese monoxide are 6 grams and 34 grams, respectively, making their mass ratio 1.5:8.5. The carbon content of the product at this ratio is estimated to be approximately 15%. The prepared composite material is labeled MnxOy@EG-3.
[0050] Comparative Example 1
[0051] The preparation method of this comparative example is basically the same as that of Example 1, except that all the expanded graphite is replaced with manganese monoxide, and the mass of manganese monoxide added is 40 grams. Other steps are the same as those of Example 1; the prepared composite material is labeled as MnxOy.
[0052] Comparative Example 2
[0053] In this comparative example, manganese monoxide was used directly as the electrode active material. The composite electrode was prepared according to the following method: manganese monoxide, acetylene black, and polyvinylidene fluoride were uniformly mixed in a mass ratio of 80:10:10. Then, an N-methylpyrrolidone solution was added, and a uniform slurry was formed under magnetic stirring. The slurry was coated onto copper foil and finally dried in a vacuum oven at 100°C for 12 hours to obtain the composite electrode.
[0054] Comparative Example 3
[0055] The preparation method of this comparative example is basically the same as that of Example 2, except that in this comparative example, expanded graphite and manganese monoxide are only uniformly mixed, and ball milling is not performed on a planetary ball mill. The prepared composite material is labeled as MnO@EG.
[0056] Experimental Example 1
[0057] This experimental example mainly studies the physicochemical properties of MnxOy@EG-2 prepared in Example 2, as follows:
[0058] 1. Morphology and microstructure characterization of MnxOy@EG-2
[0059] The morphology and microstructure of MnxOy@EG-2 were characterized using X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The results are as follows: Figures 1-4 As shown.
[0060] Figure 1 The XRD patterns of MnxOy@EG-2, standard manganese tetroxide, and manganese monoxide are shown. As can be seen from the figure, the characteristic peak positions of MnxOy@EG-2 correspond one-to-one with the positions of the manganese tetroxide standard card (JCPDS no. 24-0734) and the manganese monoxide standard card (JCPDS no. 07-0230), indicating that MnxOy@EG-2 contains manganese tetroxide and manganese monoxide.
[0061] Figure 2 The image shows a SEM image of MnxOy@EG-2. It can be seen that manganese oxide nanoparticles are uniformly embedded in the interlayer of expanded graphite and adhere to its sheet surface and edges. The average size of the manganese oxide nanoparticles is approximately 50 nm.
[0062] Figure 3 The TEM image of MnxOy@EG-2 also shows manganese oxide nanoparticles with an average diameter of about 50 nm embedded in the expanded graphite sheets, with some distributed on the surface of the sheets. This is consistent with... Figure 2 The SEM results were completely consistent, further confirming the formation of the composite structure.
[0063] Figure 4 The HRTEM image of MnxOy@EG-2 clearly shows the heterostructure interface between MnO and Mn3O4 (as shown by the white dashed lines). Among them, the stripes with a lattice spacing of 0.22 nm correspond to the (200) crystal plane of MnO, while the stripes with a spacing of 0.49 nm belong to the (101) crystal plane of Mn3O4.
[0064] Experimental Example 2
[0065] A lithium-ion battery was assembled using MnxOy@EG-2 electrode as the working electrode and lithium metal sheet as the reference / comparison electrode. The electrochemical performance of each lithium-ion battery was tested under the following conditions: constant current charge-discharge test (GCD) was performed on the Xinwei Battery Test System, with a test voltage range of 0.01 to 3.00 V.
[0066] Figure 5 The electrochemical performance test results of the prepared MnxOy@EG-2 as a negative electrode for lithium-ion batteries are shown; among them, Figure 5a shows the charge-discharge curves of MnxOy@EG-2 as the negative electrode of a lithium-ion battery at 0.3 A / g. The charge-discharge curves show that MnxOy@EG-2 has excellent cycle stability. Figure 5 b represents the rate performance of MnxOy@EG-2 as the negative electrode of a lithium-ion battery at different current densities. The rate performance graph shows that at 0.2 A g... -1 0.4A g -1 0.5A g -1 1.0A g -1 2.0A g -1 The specific capacities at the current densities were 899.4 mAh / g, 887.3 mAh / g, 842.9 mAh / g, 715.8 mAh / g, and 547.4 mAh / g, respectively. Figure 5 c represents MnxOy@EG-2 used as the negative electrode in a lithium-ion battery at 0.3 A g. -1 The cycling performance graph at current density shows that after 60 cycles, the MnxOy@EG-2 anode has a high specific capacity of 957.7 mAh / g, demonstrating excellent cycling stability. Figure 5 d demonstrates MnxOy@EG-2 as a lithium-ion battery anode at 1.0 A g. -1 Cycling performance at current density; where the lithium-ion battery is first tested at a current density of 0.2 A g. -1 The material was cycled twice to better activate it. After the third cycle, the discharge specific capacity was 684.7 mAh / g, and then at 1.0 A g. -1 After 270 cycles at the current density, the discharge specific capacity reached 742.8 mAh / g, with a capacity retention of 108% (compared to the third cycle). This increase in specific capacity can likely be attributed to material activation and the oxidation of manganese to higher valence states. This result also demonstrates that the electrode exhibits excellent cycle life and high specific capacity at high current densities.
[0067] The electrochemical performance comparison table of MnxOy@EG-1, MnxOy@EG-3, MnxOy, unmilled MnO, and MnO@EG as lithium-ion battery anodes is shown below. (At a current density of 0.3 A g) -1 After 60 cycles, the specific capacities were 691.9 mAh / g, 453.5 mAh / g, 346.3 mAh / g, 52.6 mAh / g, and 778.7 mAh / g, respectively. These results are significantly lower than the reversible specific capacity (957.7 mAh / g) of MnxOy@EG-2 as the anode in lithium-ion batteries at the same current density. Furthermore, in terms of rate performance, the current density was 0.2 A g. -1 0.4A g-1 0.5A g -1 1.0A g -1 2.0A g -1 At that time, the reversible specific capacity of MnxOy@EG-1, MnxOy@EG-3, MnxOy, unmilled MnO, and MnO@EG as negative electrodes of lithium-ion batteries was still much smaller than that of MnxOy@EG-2 as a negative electrode of lithium-ion batteries. This indicates that MnxOy@EG-2 is the composite material with the optimal mass ratio, and also shows that this structure has strong stability.
[0068] Table 1 below shows the reversible discharge specific capacity results of the electrodes provided in each embodiment and comparative example under different conditions.
[0069] Table 1 Performance test results of different electrodes
[0070]
[0071] Note: In Table 1, the reversible discharge specific capacity 1 refers to the capacity of the corresponding lithium-ion battery negative electrode at a current density of 0.3 A g. -1 The reversible discharge specific capacity after 60 cycles; the reversible discharge specific capacity 2 refers to the capacity of the corresponding lithium-ion battery anode at a current density of 0.2 A g. -1 0.4A g -1 0.5A g -1 1.0A g -1 2.0A g -1 The reversible discharge specific capacity at the 5th cycle under the given conditions.
[0072] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for preparing a manganese oxide heterojunction / expanded graphite composite material, characterized in that, Includes the following steps: Expanded graphite, manganese monoxide, and a liquid medium are mixed and then subjected to mechanochemical ball milling to obtain a manganese oxide heterojunction / expanded graphite composite material. The mechanochemical ball milling is carried out in a planetary ball mill at a speed of 200-800 rpm for 2-48 hours.
2. The preparation method according to claim 1, characterized in that, The mass ratio of expanded graphite to manganese monoxide is 1.5~4:6~8.
5.
3. The preparation method according to claim 1, characterized in that, The liquid medium is selected from at least one of water, ethanol and acetone; the ratio of the total mass of the expanded graphite and the manganese monoxide to the mass of the liquid medium added is 1:0.1~1.
4. The preparation method according to claim 1, characterized in that, The mechanochemical ball milling treatment was carried out at room temperature.
5. The preparation method according to claim 1, characterized in that, In the mechanochemical ball milling process, the grinding balls are made of agate; the ratio of the total mass of the expanded graphite, manganese monoxide, and liquid medium to the amount of grinding balls added is 1:5~50.
6. A manganese oxide heterojunction / expanded graphite composite material, characterized in that, It is prepared according to any one of claims 1 to 5.
7. The manganese oxide heterojunction / expanded graphite composite material according to claim 6, characterized in that, Manganese oxide heterojunctions are embedded or attached to the sheet structure of expanded graphite and to the surface of expanded graphite.
8. The manganese oxide heterojunction / expanded graphite composite material according to claim 6, characterized in that, The manganese oxide heterojunction includes at least two crystalline phases selected from MnO, Mn3O4, Mn2O3, and MnO2.
9. A negative electrode for a lithium-ion battery, characterized in that, The negative electrode includes a negative electrode active material, which includes the manganese oxide heterojunction / expanded graphite composite material as described in any one of claims 6 to 8, or the manganese oxide heterojunction / expanded graphite composite material prepared by the preparation method according to any one of claims 1 to 5.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode for a lithium-ion battery as described in claim 9.